2013
DOI: 10.1007/s13277-013-1335-5
|View full text |Cite
|
Sign up to set email alerts
|

MACC1 is involved in the regulation of proliferation, colony formation, invasion ability, cell cycle distribution, apoptosis and tumorigenicity by altering Akt signaling pathway in human osteosarcoma

Abstract: There is mounting evidence that metastasis-associated in colon cancer-1 (MACC1) plays pivotal roles in development and progression of many tumors, particularly in osteosarcoma (OS). However, its precise roles and molecular mechanisms remain to be delineated in OS. In the current study, we found that the levels of MACC1 mRNA and protein in four OS cell lines (MG-63, HOS, SaOS-2 and U2OS) were significantly higher than that in hFOB1.19 osteoblast (P < 0.05). The vector pcDNA-MACC1 contributed to the increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…MACC1, first identified as a colon cancer oncogene, potentially functions as an early diagnosis biomarker and is associated with the progression of multiple solid tumors (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Stein et al (12) demonstrated that MACC1 upregulation was associated with benign-malignant tumor transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MACC1, first identified as a colon cancer oncogene, potentially functions as an early diagnosis biomarker and is associated with the progression of multiple solid tumors (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Stein et al (12) demonstrated that MACC1 upregulation was associated with benign-malignant tumor transition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that MACC1 is associated with the Akt and Ras/EPH receptor B2 signaling pathways (28)(29)(30). Zhang et al (28) demonstrated that MACC1 expression may affect the PI3K/Akt signaling pathway and the protein expression of matrix metallopeptidase (MMP)2 and MMP9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified several candidate gene targets for osteosarcoma gene therapy (12)(13)(14). For example, the proliferation inhibition of osteosarcoma U2OS cells has been associated with the repression of G 1 /S cell cycle transition mediated by the overexpression of connexin43 (12).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of S100 calcium binding protein A4 is correlated with the reduced proliferation and invasiveness of osteosarcoma MG-63 cells (13). Following the loss of MACC1 MET transcriptional regulator, osteosarcoma cells were demonstrated to be less proliferative and more apoptotic, and exhibited lower colony-forming and invasive abilities (14). However, there are only a few potential therapeutic targets for osteosarcoma, thus the identification of novel candidate genes is warranted to provide more viable clinical therapeutic strategies for the treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%